Real-world multicenter study of rezvilutamide plus androgen deprivation therapy in Chinese patients with high-volume metastatic hormone-sensitive prostate cancer - Peng, Shuang; Zhang, Ruochen; Zou, Zijun; Wei, Qichen; Dai, Caixia; Wu, Jinfeng; Ye, Liefu; Wei, Yongbao; Huang, Li (Frontiers in Oncology, 2025)
BackgroundRezvilutamide combined with androgen deprivation therapy (ADT) has become a first-line standard regimen for high-volume metastatic hormone-sensitive prostate cancer (mHSPC), but real-world evidence from China remains limited.MethodsThis was a multicenter, retrospective real-world cohort study enrolling high-volume mHSPC patients diagnosed and treated with rezvilutamide plus ADT at multiple tertiary hospitals in China from August 2023 to March 2025. Baseline demographics, tumor burden, treatment regimen, and follow-up data were collected. The primary endpoints were 3-month PSA responses (PSA50, PSA90, PSA ≤0.2 ng/mL), subgroup efficacy, and adverse event rates. Multivariable logistic regression was used to identify independent predictors for achieving PSA ≤0.2 ng/mL at 3 months. Efficacy and safety outcomes were compared with major randomized controlled trials (RCTs) and other real-world studies.ResultsA total of 236 patients with high-volume mHSPC were enrolled, with a median age of 74.9 years. The rates of achieving PSA50, PSA90, and PSA ≤0.2 ng/mL at 3 months were 99.15%, 88.98%, and 39.41%, respectively. Subgroup analysis showed consistent efficacy across age, ECOG, and Gleason strata, with only lower baseline PSA predicting higher likelihood of undetectable PSA. Multivariable analysis further indicated that baseline PSA showed a trend toward being an independent predictor for achieving PSA ≤0.2 ng/mL (P=0.063). The incidence of any-grade and grade 3–4 adverse events was 65% and 23%, respectively, with no new severe safety signals observed. All results were highly consistent with RCTs such as CHART.ConclusionRezvilutamide plus ADT provides rapid and profound PSA responses with a favorable safety profile in real-world Chinese patients with high-volume mHSPC. Baseline PSA serves as an important predictor for short-term biochemical response, supporting its clinical value as a standard first-line therapy.